Australian Women Journalists and the "Pretence of Equality". (1st May 2015) - Baker, Jeannine
Abstract : Australian women journalists were granted equal pay for equal work in 1917, under the first federal award for journalists. This article analyses the role of women in Australian journalism in the first half of the twentieth century and reveals that behind the appearance of gender equality is a history of persistent discrimination. Between the wars most women journalists were confined to work considered to be of lesser value, typically on the women's pages of daily newspapers, and had limited opportunities for advancement to higher paid positions. Although World War II enabled many women journalists to move into higher status positions, they continued to be perceived according to gendered assumptions about their roles, modes of behaviour and abilities. War also reinforced anxieties about the disruption of normal gender divisions within the newspaper office.